Customer Value in Social Media Marketing and Service Quality Effects on Britama Prioritas Decisions at BRI Sukabumi - Alya Aprilianti; Agus Setyo Pranowo; Jan Horas V. Purba (Economics and Business Journal (ECBIS), 2026)
This study examines the role of customer value in mediating the relationship between social media marketing and service quality toward the decision to become a BritAma Prioritas customer at Bank Rakyat Indonesia Sukabumi Branch. The key issue addressed in this study is the need to understand how digital marketing communication and priority banking service quality can be converted into meaningful value that influences premium customer decisions. This research employed a quantitative explanatory approach involving 386 BritAma Prioritas customers as respondents. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using Confirmatory Factor Analysis and Structural Equation Modeling. The results show that social media marketing and service quality have positive and significant effects on customer value. Social media marketing, service quality, and customer value also positively and significantly influence customer decision. Customer value was found to be the strongest predictor of customer decision and significantly mediated the effects of both social media marketing and service quality. These findings indicate that customer acquisition in priority banking depends not only on promotional activities and service performance, but also on customers’ holistic value evaluation.